2020
DOI: 10.1080/17441692.2020.1724316
|View full text |Cite
|
Sign up to set email alerts
|

The Ashodaya PrEP project: Lessons and implications for scaling up PrEP from a community-led demonstration project among female sex workers in Mysore, India

Abstract: To inform PrEP roll out, Ashodaya Samithi, a sex workers' collective, conducted a community-led prospective demonstration project among female sex workers in Mysore and Mandya, India. Following a community preparedness phase and pre-screening, participants were recruited for clinical screening and enrolment, provided PrEP as part of combination HIV prevention, and followed for 16 months. Adherence was measured by self-reported pill intake and by tenofovir blood level testing among a subset of participants. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…33 A similar study to ours was conducted in South India, led by a long standing community-owned HIV prevention organization, and it also demonstrated both high levels of adherence as well as retention. 13 There was no evidence of significant changes in selfreported sexual behavior or other measured risk factors, such as alcohol and drug abuse. While these reports could have been distorted by lack of blinding or social desirability bias, the proportion of women treated for STIs, a more objective marker for sexual risk behavior, declined significantly over time, supporting the notion that PrEP use was not associated with increased risk in sexual behavior.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…33 A similar study to ours was conducted in South India, led by a long standing community-owned HIV prevention organization, and it also demonstrated both high levels of adherence as well as retention. 13 There was no evidence of significant changes in selfreported sexual behavior or other measured risk factors, such as alcohol and drug abuse. While these reports could have been distorted by lack of blinding or social desirability bias, the proportion of women treated for STIs, a more objective marker for sexual risk behavior, declined significantly over time, supporting the notion that PrEP use was not associated with increased risk in sexual behavior.…”
Section: Discussionmentioning
confidence: 86%
“…However, only one study to date has evaluated the use of oral PrEP by FSWs or other high-risk populations in India. 13 In this study, we present the results of a demonstration trial in Kolkata, India, designed to assess the feasibility and impact of delivering PrEP, integrated within an existing community-based HIV prevention program for FSWs in Kolkata, the capital of West Bengal, and one of the largest cities in India (population 15 million). We assessed whether daily oral PrEP could be added in a safe and effective manner to a package of HIV preventive interventions for FSWs.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately half of the clients in this study reported side effects which they linked to the ARV use. The predominance of gastrointestinal issues is common across the literature, but this rate is higher than that reported in trials and in Australian and Indian demonstration projects, where side effects occurred in around one third of persons ( 22 , 29 , 31 ). The discrepancy may be explained by reported side-effects being actually unrelated to ARV use and recall bias given the length of time between initiation and follow up (3 months).…”
Section: Discussionmentioning
confidence: 74%
“…The efficacy of PrEP has been conclusively shown in clinical trials, such as the iPrEx, IPERGAY and Partners PrEP, but reports from real-world implementation have only been available for around five years and largely focused on demonstration projects which are smaller scale research endeavours designed to assess acceptability, cost and program design for scale-up ( 21 , 22 ). This study is the first of its kind in the English-speaking Caribbean and while the uptake rate is narrowly defined as those who initiated PrEP from among those formally assessed for eligibility (as opposed to anyone who had enquired about PrEP or been told about the intervention, which was impossible to ascertain), the excellent rate of uptake demonstrates the widescale acceptability of PrEP in Barbados, which has a largely Black population of African descent, and in both men and women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation